Study on the Support System Mechanism of Entry Roof with Roof Cutting Pressure Releasing Gob-Side Entry Retaining Technology - Xingen Ma; Guihe Li; Haitao Cao; Haijun Wang; Xiangyuan Shi; Qingquan Zhao; Zhengcan Han; Tianyi Zhang; Weiping Dai; Jiangling Zhang (Advances in Civil Engineering)
To improve the technical system of the roof cutting pressure releasing gob-side entry retaining technology (RCPRGERT) and provide reference for the adaptive promotion and optimization of the new technology, the entry support system mechanism with RCPRGERT is studied in this paper. Firstly, the stress structure of the roof cutting short beam is analyzed by the mechanical theory analysis method. Then, taking 8304 working face of Tashan Coal Mine as an example, the stress distribution characteristics of the surrounding rock in different entry retaining stages are simulated by numerical simulation, which provides an important reference for the field support design and puts forward an idea of hierarchical support. Finally, an engineering test is carried out in the experimental working face to verify the design of the retaining entry support, which obtains a well entry retaining effect. The research results in this study provide powerful theoretical and practical references for the promotion of RCPRGERT under similar geological conditions.